Knowledge in the Making. On Production and Communication of Knowledge in the Material Practices of Architecture - Nilsson, Fredrik (FormAkademisk, 2013)
This article discusses some conceptualframeworks and notions used in, or with the potential to further develop,theories and understandings regarding the specific processes and forms ofknowledge in creative practices of architecture, design and art. Morearticulate conceptual frameworks are not only of importance for strengtheningdisciplines and practices, but can also make valid contributions in widersocietal contexts in relation to contemporary challenges in built environments.With the point of departure in the notions “material practice” by Stan Allenand “making disciplines” by Halina Dunin-Woyseth, theoretical frameworks andapproaches by, for example, Andrew Pickering, Nigel Cross, Albena Yaneva, andGilles Deleuze & Felix Guattari are discussed. The contemporary world hasbrought challenging societal developments and complex transformations of builtenvironments, but new tools have also enabled other forms of design experiments,including non-verbal languages and various model worlds. The article arguesthat we must constantly study the contemporary situation, but also reflect uponour means of designing and production, as well as our forms of working andcollaboration. New relationships between theory and practice, between researchand practical designing, between academia, architectural practice and differentactors in society, must be articulated and established through consciousstrategies.